Consumption and income over the lifecycle in Nigeria (2011)
This paper utilises National Transfer Accounts framework to estimate age profiles of consumption and income over the lifecycle in order to determine actual period of dependency in Nigeria. The paper quantifies inter-age monetary flows of consumption and labour income and subsequent economic lifecycle deficit and the implications this will have for social policy and human capital development. The results indicate that given the profiles of consumption and income over the lifecycle in Nigeria, child dependency is for the first 33 years of life while old-age dependency occurs from 63 years upwards. The period of lifecycle surplus span 30 years from 33-63 years. The structure of consumption and income flows reveals that Nigeria has a lifecycle deficit of N3.5 trillion in 2004. Since the population is highly skewed towards children, inter-generational flows are heavily skewed downwards. The deficits must then be covered through age reallocations of transfers and asset income.